Normative cardiorespiratory values in Italian first-division male soccer players: effects of age, playing position and season phase - Di Paco, Adriano; Laveneziana, Pierantonio; Onorati, Paolo; Trotta, Luca; Boccia, Gennaro (Biology of Sport, 2025)
The study aimed to provide reference values of cardiorespiratory parameters and maximal exercise velocity (MEV) of first-division soccer players measured during a ramp exercise running test. A large ( N = 741) database of cardiopulmonary exercise tests collected over a decade on Serie A teams in Italy was scrutinized. The reference values were stratified for age, playing position, and season phase. We found an average V̇O 2 peak of 4.78±0.56 l/min, a relative V̇O 2 peak of 61.5±5.96 ml/kg/min and an MEV of 19.0±1.3 km/h. Relative V̇O 2 peak was constant from 18 to 30 years of age and then decreased, while MEV decreased constantly with increasing age. While the absolute V̇O 2 peak was similar for all playing roles (P = 0.782), the midfielders were the players with the highest relative V̇O 2 peak ( P = 0.020) and they had lower body mass than the others ( P < 0.001). This study presents estimates of the influence of age, player position, and season phase on V̇O 2 peak in men’s elite soccer. V̇O 2 peak values ~62 ml/kg/min fulfil the demands for V̇O 2 peak in men’s professional soccer. Midfielders showed larger relative, but not absolute, V̇O 2 peak.